Horizontal and Vertical Transmission of Powassan Virus by the Invasive Asian Longhorned Tick, Haemaphysalis longicornis, Under Laboratory Conditions - Raney, Wilson R.; Herslebs, Erik J.; Langohr, Ingeborg M.; Stone, Madeline C.; Hermance, Meghan E. (Frontiers in Cellular and Infection Microbiology, 2022)
The Asian longhorned tick, Haemaphysalis longicornis, is an ixodid tick native to East Asia that was first detected in North America outside a port of entry in 2017. This invasive species has since been detected in 17 states. As the invasive range of the tick continues to expand, the vector competence of H. longicornis for pathogens native to North America must be assessed. Here, we evaluate the vector competence of H. longicornis for Powassan virus (POWV) under laboratory conditions. POWV is a North American tick-borne flavivirus that is typically transmitted through the bite of Ixodes species ticks. The invasive range of H. longicornis is expected to overlap heavily with the geographic range of Ixodes scapularis and POWV cases, highlighting the potential for this invasive tick species to amplify POWV transmission in natural foci should the native tick vectors and H. longicornis share similar hosts. In these studies, adult female H. longicornis ticks were infected with POWV via anal pore microinjection. Viral RNA and infectious virions were detected in tick tissues via q‐RT‐PCR and focus‐forming assay, respectively. POWV‐injected female ticks were infested on mice, and virus was transmitted to mice during tick feeding, as shown by clinical signs of disease and seroconversion in the tick-exposed mice, as well as the detection of viral RNA in various mouse tissues. A POWV-injected female tick transmitted virus to her larval progeny, indicating that H. longicornis can vertically transmit POWV. These naturally-infected larval ticks were also able to transmit POWV to the mouse on which they fed and to the nymphal stage after molting, further demonstrating that H. longicornis can transmit POWV in the horizontal and transstadial modes. Larval and nymphal ticks were also orally infected with POWV while feeding on viremic mice. Additionally, this study provides the first report of POWV neuropathology based on a natural tick transmission model of POWV. Together, our results suggest that the invasive H. longicornis tick is a competent vector of POWV. These findings underline the growing danger this tick may pose to human health in the United States. Additional scholarship on the tick’s biology, ecology, and pathogen transmission dynamics in nature will be important towards understanding the full public health impact of this invasive species.